The influence of recipe disaggregation in dietary assessment: results from the national food consumption survey in Saint Kitts and Nevis - Crispim, Sandra Patricia; Elias, Vanessa Cardozo Mendes; Matthew-Duncan, Latoya; Francis-Grandeson, Isabella; Jean, Fransen; de Quadros, Victoria Padula; Balcerzak, Agnieszka; de Sousa, Rita Ferreira; Frauches, Ariel de Moraes; Almeida, Claudia Choma Bettega; Hutchinson, Sharon D.; Charrondière, U. Ruth; et al. (Frontiers in Nutrition, 2024)
It is not always the case that recipe disaggregation is performed in dietary surveys. This investigation aimed to assess the influence of recipe disaggregation in the 2020-2021 national dietary survey in Saint Kitts and Nevis, and provide recommendations for future assessments. A total of 1004 individuals provided information on their food consumption obtained using 24-hour dietary recalls, and 442 recipes were reported. Some recipes were reported as single ingredients at the data collection stage (n=65). In most cases, the respondent provided a standard recipe without disaggregation (n=377). A simple and pragmatic recipe disaggregation methodology was developed. The procedure of recipe disaggregation comprised nine steps, including identifying recipes, ingredients, quantities, conversion factors, and the presence of visible fluid, among others. Seventy-eight non-disaggregated standard recipes were post-disaggregated (21% of recipes) to identify ingredient weights. Either the chi-square or Fisher's exact tests were applied to assess the significance of differences in frequency of food group consumption before and after disaggregation. The proportion of consumers across the different food groups increased dramatically for some food groups after recipe disaggregation, with significant differences (all p<0.01) for cereals and their products (81.3% before and 94.7% after), eggs and their products (21.7% before and 34.6% after), fats and oils (6.9% before and 44.5% after), fish, shellfish and their products (26.7% before and 38.5% after), meat and meat products (59.7% Formatado: Português (Brasil)